Contraception in adolescence: the influence of parity and marital status on contraceptive use in 73 low-and middle-income countries - Carolina de Vargas Nunes Coll; Fernanda Ewerling; Franciele Hellwig; Aluísio Jardim Dornellas de Barros (BMC, 2019)
Abstract Background There is still a large gap in relation to effectively meet the contraceptive needs and family planning goals of adolescents. Our aim was to describe how having a partner and children impact on contraceptive behavior of sexually active female adolescents from low and middle-income countries (LMICs). Methods Analyses were based on the most recent Demographic and Health Surveys and Multiple Indicator Surveys carried out since 2005 in 73 LMICs with available data for sexually active women aged 15-19 years. Modern contraceptive prevalence and demand for family planning satisfied with modern methods of contraception (mDFPS) were estimated among three subgroups of adolescents considering their parity and marital status- not married, married without children, and married with children - at national and regional levels. Results Female adolescents who were married with no children presented the lowest median modern contraceptive prevalence in all world regions, ranging from 2.9% in West & Central Africa to 29.0% in Latin America & Caribbean. Regarding mDFPS, the lowest coverage for married adolescents without children was found in West & Central Africa (12.6%), whereas Latin America & Caribbean presented the highest (50.4%). In East Asia & Pacific, not married adolescents were the group with the lowest mDFPS (17.1%). In 12 countries, mDFPS was below 10% among married adolescents without children: Angola, Chad, Congo, Congo DR, Guinea, Mozambique, Niger, Nigeria, and Senegal in Africa, Philippines and Timor-Leste in Asia and Guyana in Latin America & Caribbean. Conclusions In most countries, modern contraceptive prevalence and mDFPS were particularly low among married female adolescents without children, which should be considered a priority group for intervention. The findings suggest that social norms regarding marriage and fertility expectations and other cultural barriers have a role at least as relevant as contraceptive availability. All these aspects need to be considered in the design of family planning strategies to effectively increase modern contraceptive use among adolescents everywhere, particularly in conservative contexts.